2010
DOI: 10.1161/circep.109.868356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Left Atrial Lesions After Initial and Repeat Atrial Fibrillation Ablation

Abstract: Background We evaluated scar lesions following initial and repeat catheter ablation of atrial fibrillation (AF) and correlated these regions to low-voltage tissue on repeat electroanatomical (EA) mapping. We also identified gaps in lesion sets that could be targeted and closed during repeat procedures. Methods and Results One hundred forty-four patients underwent AF ablation and received a delayed-enhancement MRI (DE-MRI) at three months post-ablation. The number of pulmonary veins (PV) with circumferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
69
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(72 citation statements)
references
References 29 publications
0
69
2
Order By: Relevance
“…13) [74]. However, this is difficult to achieve, with only 7% of the patients having complete scarring of all veins in one study [75].…”
Section: Dmentioning
confidence: 96%
“…13) [74]. However, this is difficult to achieve, with only 7% of the patients having complete scarring of all veins in one study [75].…”
Section: Dmentioning
confidence: 96%
“…In many patients, only repeated procedures can suppress the arrhytmia. 10 A prospective multicenter study that included 167 patients with paroxysmal atrial fibrillation, comparing PVI with antiarrhythmic medication, showed that 66% of subjects had better results following ablation during the 9 months of follow-up, compared to patients that had received antiarrhythmic drugs. 11 Currently the most challenging task is to parallelly improve ablation techniques, as well as to find new arrhythmia substrates and to reduce the recurrence rates of atrial fibrillation.…”
Section: Catheter Ablation In Afmentioning
confidence: 99%
“…The ability to perform gap visualization post ablation remains an issue of ongoing debate, and in this study similar to the study by Sprague et al, 8 CMR was not able to reliably identify conducting gaps. In contrast, studies by Bisbal et al, 7 Badger et al, 9 and Taclas et al 10 showed good correlation between electroanatomic mapping and LGE CMR to predict gap location (Table). Some reasons may be technical and the different image acquisition protocols, scar reconstruction algorithms, LGE and electroanatomic mapping threshold values, scan resolution and magnetic resonance imaging scan timing make a comparison difficult.…”
mentioning
confidence: 94%
“…6 Identification of such gaps by noninvasive techniques, such as cardiac magnetic resonance imaging (CMR), would have high clinical utility. [7][8][9][10][11] Article see p 270…”
mentioning
confidence: 99%